Chemistry and the everyday - Leite, Fernanda Fernandes (Scientia cum Industria, 2016)
This paper presents a work proposal, using simple products every day to conducting the study of chemical. The workshop is intended to motivate teachers to work with students in the classroom, making the class more attractive and meaningful learning. The methodology applied in this workshop was for questioning, the participants into groups performed practical experiments on the glue made with casein milk, the various colors of chemicals, the pH of the products used daily for all of us and to compare the foam biodegradable detergent and conventional. Teachers from different areas of knowledge participated in the workshop, which provided an interdisciplinary discussion. There were moments of practical activities and other reflective on the techniques used and the challenges that can be offered to students in the classroom. The questions enabled the interaction between the participants, who took advantage of the knowledge of each area for further http://dx.doi.org/10.18226/23185279.v3iss3p117